The immanent stage of the Aesthetics of San Buenaventura from its sources of inspiration - Salvador-González, José María (Revista de Filosofía, 2022)
Among the vast theoretical corpus of the Franciscan thinker St. Bonaventure of Bagnoregio, we have focused our attention here on the book entitled Itinerarium mentis in Deum (1259) because in it, our author condenses the essential nucleus of his peculiar Aesthetics. Restricting, even more, the investigative approach, in the present article, we limit ourselves to analyze the first of the three phases or levels in which Bonaventure structures his Aesthetics, namely, the degree that we could call immanent Aesthetics. According to the author, the human being can access the knowledge of God if he considers material beings as vestiges and beautiful images that visibly reflect the invisible divine beauty. In the second part of our article, we try to highlight some theses of previous philosophers who seem to have almost certainly inspired St. Bonaventure in the basic statements of his immanent Aesthetics.
Keywords: aesthetics; created world; material beings; vestige; image; God